Pengaruh Growth, Kebijakan Dividen, Leverage, Profitability Pada Perusahaan Manufaktur - Yolanda Chintia Lolowang, Rini Tri Hastuti (Jurnal Paradigma Akuntansi, 2019)
The Company has a long-term goal to maximize a company. This study aims to determine the effect of growth, dividen policy, leverage and profitability of the company to corporate value. The study sample as many as 41 companies conducted in manufacturing companies listed on the Indonesia Stock Exchange. Observation period 2015 to 2017. The research hypothesis testing using analysis techniques multiple linear regression and t test to see the effect of company’s growth, dividen policy leverage, and profitability on the firm value. The results showed that: (1) the growth positive effect was not significant to the value of the company (2) the dividen policy positive effect was not significant to the value of the company (3) the leverage has a positive effect significant to the value of the company (4) the profitability has a positive effect significant to the value of the company.